(Invited) Characteristics of a Wire-Bonding-Less SiC Power Module Operating in a Wide Temperature Range. (21st September 2015) - Sato, Shinji; Tanisawa, Hidekazu; Anzai, Takeshi; Takahashi, Hiroki; Murakami, Yoshinori; Kato, Fumiki; Watanabe, Kinuyo; Sato, Hiroshi
Abstract : Using high-speed switching, SiC power devices can reduce on-resistance in the on-state to realize low power converter losses. In addition, SiC power devices can be operated in high temperatures; thus, their cooling systems can be reduced in size or removed altogether, thereby increasing the power density of the power converter. The authors have studied a power module and power converter using properties of SiC power devices, and have previously proposed a power converter having high power density with a power module that is capable of high temperature operation, a gate driving technique for SiC power devices to prevent false turn-on with high-speed switching, and development of a noise filter for high-speed switching or high-frequency switching. In this study, we designed and fabricated a SiC power module with a built-in snubber circuit. This power module is operable in high temperatures over 200 °C.